2021
DOI: 10.3390/diagnostics11091596
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regional Pain Syndrome Type I Following Non-Orthopedic Surgery: Case Report and Narrative Review

Abstract: Complex regional pain syndrome type I (CRPS I)—or algodystrophy—is a rare disease that usually occurs after a traumatic event. It is characterized by typical clinical findings such as severe and disabling pain disproportionate to the injury, functional limitations, as well as sensory and vasomotor alterations. However, some people do not report any injury associated with algodystrophy onset in personal history. We describe the management of an unusual case of CRPS I which occurred during the long-term follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Cases of CRPS following surgery or other invasive procedures in non-orthopedic settings are rare and often underestimated [13] . Some have been described, for example, after percutaneous transluminal coronary angioplasty, coronary artery injections, cardiac ablation, fistula/graft for hemodialysis, renal and bone marrow transplantation, mastectomy, and thoracic surgery.…”
Section: Algodystrophy In the Non-orthopedic Settingmentioning
confidence: 99%
“…Cases of CRPS following surgery or other invasive procedures in non-orthopedic settings are rare and often underestimated [13] . Some have been described, for example, after percutaneous transluminal coronary angioplasty, coronary artery injections, cardiac ablation, fistula/graft for hemodialysis, renal and bone marrow transplantation, mastectomy, and thoracic surgery.…”
Section: Algodystrophy In the Non-orthopedic Settingmentioning
confidence: 99%
“…Finally, as an underestimated consequence of trauma or orthopedic intervention, Complex Regional Pain Syndrome type I (CRPS I) might occur, with typical findings consisting in severe pain, functional limitation, and vasomotor alteration [ 28 ]. In some cases, however, this condition might also be related to non-orthopedic procedures, as depicted by Moretti et al [ 29 ] in a recent case report, describing a case of CRPS I spontaneously following percutaneous transluminal coronary angioplasty, in a 44-year-old man approximately 5 months after the event. Bone scan might be crucial in diagnosing controversial cases, along with a comprehensive clinical and instrumental evaluation.…”
Section: Diagnostics In Bone Diseasesmentioning
confidence: 99%
“…In addition, surgical methods may have an impact on incidence of CRPS I. [14][15][16] Jo et al 17 reported that the incidence of CRPS-1in distal radius fractures patients was higher after open reduction than after closed reduction. Therefore, we focused on the incidence of CRPS I after radial head arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…However, acutely injured patients often experience secondary injury, mostly caused by ongoing tissue trauma during surgical preparation, related inflammatory reaction, hypovolemia due to blood loss and other causes. In addition, surgical methods may have an impact on incidence of CRPS I 14–16 . Jo et al 17 .…”
Section: Introductionmentioning
confidence: 99%